Tinjauan Ketersediaan Jalur Evakuasi Bencana Pada Bangunan Gedung Rektorat Universitas Teuku Umar - Edi Mawardi; Samsunan Samsunan; Risma Ramadhan (Litbang Pemas - Universitas Islam Lamongan, 2019)
A disaster is an event or series of events that threaten and disrupt people's lives and livelihoods caused by both natural and non-natural factors as well as human factors. Disasters can result in human casualties, environmental damage, property losses, and psychological impacts. Disasters are categorized into 3 (three), namely natural disasters, social disasters and non-natural disasters. The purpose of this study was to determine the availability and completeness, conditions and suitability between the use and function of the rescue path in the Teuku Umar Rectorate Building Building based on applicable regulations. The research method used is a quantitative method. The data used are primary and secondary data, taken by distributing questionnaires, observations and direct observations. Questions through the questionnaire were processed using SPSS-23 software. While the data from the results of observations and direct observations, are processed through analysis of descriptions in accordance with field results. All valid questions have a correlation value greater than the value of the product moment / r table 0.361. The results showed that the availability and completeness of the rescue path at the Teuku Umar University Rectorate Building had not been fulfilled for social functions as a campus building. The condition of rescue in Teuku Umar University Rectorate Building is still very minimal, and the causal factor is constrained due to the lack of understanding of the policy of the Minister of Public Works Regulation No. 26 / RPT / M / 2008 regarding the Technical of the Rescue Facility System in Buildings and the Environment.